2018
DOI: 10.1002/eat.22926
|View full text |Cite
|
Sign up to set email alerts
|

From fad to FAD: A theoretical formulation and proposed name change for “drunkorexia” to food and alcohol disturbance (FAD)

Abstract: "Drunkorexia" is a term that has been used to describe behaviors such as restricting food intake in anticipation of alcohol consumption to offset total caloric intake, and/or to enhance the intoxicating effect of alcohol consumption. Scattered studies over the past few years have indicated the potential problematic nature of the intersection of these behaviors, yet there remain significant gaps in the operationalization of the construct, limiting research progress. In this article, we articulate limitations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 18 publications
4
31
1
Order By: Relevance
“…It could, therefore, be further suggested that Drunkorexia, therefore, acts mainly as a compensatory behaviour to mask low appearance confidence in individuals with high disinhibition levels. These are important findings; as they link to the debate as to whether Drunkorexia is driven by similar motivations as eating disorders or substance abuse disorder [16,17]. The current results now suggest that it could possibly be either a symptom of EDs, i.e., engagement in Drunkorexia to prevent weight gain from alcohol, while the disinhibition factors of increased sensation-seeking may explain the aspect of substance use as a compensatory behaviour to feel the effects of alcohol quicker (i.e., to feel better about their appearance).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It could, therefore, be further suggested that Drunkorexia, therefore, acts mainly as a compensatory behaviour to mask low appearance confidence in individuals with high disinhibition levels. These are important findings; as they link to the debate as to whether Drunkorexia is driven by similar motivations as eating disorders or substance abuse disorder [16,17]. The current results now suggest that it could possibly be either a symptom of EDs, i.e., engagement in Drunkorexia to prevent weight gain from alcohol, while the disinhibition factors of increased sensation-seeking may explain the aspect of substance use as a compensatory behaviour to feel the effects of alcohol quicker (i.e., to feel better about their appearance).…”
Section: Discussionmentioning
confidence: 91%
“…In this context, reduced eating is seen as both an inappropriate compensatory behaviour to avoid weight gain [16], and a food and alcohol disturbance [11]. While some limited research has been conducted investigating the prevalence of these behaviours, as well as underlying motivations and reasonings; many questions are left unanswered [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to our knowledge, no study so far has investigated an emerging and serious combination of disordered eating and alcohol consumption named “food and alcohol disturbance” (FAD) [ 13 ] during the lockdown, and the potential factors that may have been involved in protecting or increasing vulnerability to this behavior. Sometimes referred to also as “drunkorexia” [ 14 , 15 ], FAD concerns a variety of unhealthy eating behaviors in which people engage in preparation or in response to alcohol consumption [ 16 ], and can include calorie restriction, fasting, self-induced vomiting, use of laxatives and/or diuretics, and excessive exercising [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%